Force output in giant-slalom skiing: A practical model of force application effectiveness - Cross, M. R.; Delhaye, C.; Morin, J.-B.; Bowen, M.; Coulmy, N.; Hintzy, F.; Samozino, P. (PLOS ONE, 2021)
Alpine ski racers require diverse physical capabilities. While enhanced force production is considered key to high-level skiing, its relevance is convoluted. The aims of this study were to i) clarify the association between performance path length and velocity, ii) test the importance of radial force, and iii) explore the contribution of force magnitude and orientation to turn performance. Ski athletes (N = 15) were equipped with ski-mounted force plates and a global navigation satellite system to compute the following variables over 14 turns: path length (L), velocity normalized energy dissipation [Deltaemech/vin], radial force [Fr], total force (both limbs [Ftot], the outside limb, and the difference between limbs), and a ratio of force application (RF = Fr/Ftot). Data were course-averaged or separated into sectional turn groupings, averaged, and entered into stepped correlation and regression models. Our results support Deltaemech/vin as a discriminative performance factor (R2 = 0.50-0.74, p < .003), except in flat sections. Lower course times and better Deltaemech/vin were associated with greater Fr (R2 = 0.34-0.69 and 0.31-0.52, respectively, p < .032), which was related to both Ftot and RF (ß = 0.92-1.00 and 0.63-0.81, respectively, p < .001) which varied in predictive order throughout the sections. Ftot was associated with increased outside limb force and a more balanced contribution of each limb (ß = 1.04-1.18 and -0.65- -0.92, respectively, p < .001). Fr can be improved by either increasing total force output or by increasing technical effectiveness (i.e., proportionally more force radially) which should increase the trajectories available to the skier on the ski course.